Is the maternal 'babybrain' adaptive? : examining theory of mind, emotional state, and the association with attachment over pregnancy and the postpartum : a thesis presented in partial fulfilment of the requirements for the degree of Doctorate in Clinical Psychology, Massey University, Wellington, New Zealand - Spill, E. Kate (Massey University, 2023)
Pregnancy is a time of great maternal neuroplasticity with associated cognitive and behaviour change. Cognitive decrements are seen in memory, executive functioning, and overall cognitive functioning, and cognitive enhancements in facial and affect processing. It has been proposed that cognitive enhancements may come at the cost of cognitive decrements, due to the brain restructuring in a manner which prioritises adaptive caregiving-related functions. Hoekzema et al. (2016) found significant reductions in the grey matter (GM) volume of first-time pregnant women in the Theory of Mind (ToM) network. On the basis that reduced GM is an indicator of better processing efficiency and specialisation, they proposed that pregnancy may be a sensitive period where ToM may be enhanced to support the maternal-infant attachment relationship. ToM is a multidimensional construct which describes the capacity to understand the mental state of ourselves and others. It has been investigated in maternal-infant attachment as maternal mind-mindedness and parental reflective function. There are very few studies which have investigated individual differences in ToM over the perinatal period and its link to attachment. Objective: The primary aim of this research is to investigate ToM capacity over the perinatal period and its relationship to attachment. Method: Study 1 was a quasi-experimental, between-groups design comparing third trimester primiparous women’s performance on four ToM tasks with that of nulliparous control women. Participants (n=133; 68 pregnant) completed four computer-based ToM tasks: Reading the Mind in the Eyes-Revised (RMET), Hinting, Mind-mindedness, and the Reflective Functioning Questionnaire (RFQ). Prenatal attachment was measured with the Prenatal Attachment Inventory-Revised (PAI-R) and emotional state with the Depression, Anxiety and Stress Scale (DASS-21). It was hypothesised that: ToM would be enhanced in pregnancy; ToM would be associated with pre-natal attachment; emotional state (depression, anxiety, stress) would be negatively associated with both ToM and attachment. Results: Study 1 found no between group differences between pregnant and control participants on ToM performance. In the presence of greater depression and stress (both groups) and anxiety (pregnancy only) there was significantly more uncertainty about the mental states of self and others, an aspect of reflective function ToM. ToM in pregnancy was not consistently associated with prenatal attachment. Method: Study 2 compared ToM measured in pregnancy with caregiving ToM (Parental Reflective Functioning Questionnaire; PRFQ) and maternal-infant attachment (Maternal Postnatal Attachment Scale; MPAS) when mothers and babies were 4-6 months postpartum (n=55). It was hypothesised that ToM in pregnancy would predict parental reflective function and attachment; and that parental reflective function in the postpartum would be concurrently associated with maternal-infant attachment. Emotional state was expected to be negatively associated with both parental reflective function and attachment. Results: ToM in pregnancy had no consistent relationship to postpartum ToM (PRFQ) or attachment (MPAS). In postpartum women, the presence of poor and rigid caregiver ToM (PRFQ-Pre-Mentalising Modes) was associated with poorer quality of attachment and greater hostility in attachment (both MPAS subscales; r > .3). To explore this relationship further two mediation models were computed. These revealed that under conditions of greater depression or stress, mothers were more likely to use poorer, more rigid, and inappropriate ToM when they reflected on the inner experiences of their baby and themselves and, taken together, these factors were linked to significantly greater levels of hostility in the attachment relationship and poorer overall attachment. For each mediation model, stress and depression accounted for over a third of the basic relationship between caregiver ToM and attachment. Conclusions: (1) Contrary to Hoekzema et al. (2016), there is no evidence of general ToM enhancement in late pregnancy nor of a consistent relationship between ToM capacity in pregnancy and postpartum attachment. However, given that pregnant women were also no worse than control women, this might offer preliminary support for a cognitive prioritisation of ToM over general cognition in pregnancy. (2) In postpartum women there was a significant moderate positive relationship between parental reflective function and aspects of maternal-infant attachment. Levels of depression and stress were linked to poorer reflective function and attachment and accounted for over a third of the variance. This research is the first to examine ToM over the perinatal period using multiple measures and to examine the relationship to attachment mediated by mood state.
Keywords: Pregnancy; Puerperium; Psychological aspects; Philosophy of mind; Attachment behavior; Mother and infant; maternal cognition; theory of mind; caregiving; reflective function; mind-mindedness; perinatal emotional state; maternal-infant attachment; mediation models; 520301 Clinical neuropsychology